Metabolism of Steroid and Amino Acid Moieties of Conjugated Bile Acids in Man III. CHOLYLTAURINE (TAUROCHOLIC ACID) - Hepner, Gershon W. (1973)
After oral administration of [2,4-(3)H]-cholyl[(35)S]taurine to eight healthy subjects with indwelling nasoduodenal tubes, the specific activity of the cholyl and taurine moieties and the distribution of radioactivity in biliary bile acid and urinary metabolites, as well as total urinary and fecal (35)S and (3)H, were measured at intervals for 4-8 days. Similar measurements were made after [(35)S]taurine was given orally or intravenously or instilled into the distal intestine. The daily fractional turnover rate of the taurine moiety of cholyltaurine was low and similar to that of the cholyl moiety, indicating that deconjugation occurring during enterohepatic cycling was less than half that previously observed for glycine-conjugated bile acids. Some of the cholyl moiety was absorbed but, since reconjugation occurred predominantly with glycine, little reincorporation into the cholyltaurine pool was observed. Some of the taurine moiety was also absorbed intact but entered large taurine pools, and little reincorporation into the cholyltaurine pool was seen. Oral administration of taurine expanded the cholyltaurine pool and induced a decrease in the fractional turnover rate of the cholyl moiety of cholyltaurine, interpreted to indicate a greater reincorporation of the cholyl moiety because of increased reconjugation with taurine. Taurine moiety not absorbed as taurine appeared to be absorbed largely as sulfate which, like taurine, entered large endogenous pools. Little fecal excretion of (35)S occurred. (35)S was excreted in urine as taurine and sulfate, and excretion in the first 24 h (as percentage of administered dose) correlated highly (r = 0.93) with the daily fractional turnover rate of the taurine moiety. When taurine was instilled into the distal intestine, it appeared as such in plasma, but the more distal the site of instillation, the greater the fraction of urinary (35)S present as sulfate. The [(35)S]sulfate appeared to have come from bacterial degradation of [(35)S]taurine because, when [(35)S]taurine was given intravenously, (35)S was excreted in urine chiefly as [(35)S]taurine with little SO(4)=(-)[(35)S] being present.